Peran Pendidikan Agama Kristen Dalam Memerangi Berita Hoaks di Media Sosial - Talizaro Tafonao; Prasetyo Yuliyanto (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2020)
In this study, the author studies the role of Christian religious education in combating hoax on social media. This study begins with the author's empirical observation where these days hoax on social media becomes the main news that is endlessly discussed in public. As a result of many hoaxes on social media, there are many divisions between the people as expressed in this empirical study. If it is carefully observed that the main problem is not in the development of science and technology globally, but the problem is there are every person who uses the technology irresponsibly because humans are too spoiled with various facilities of technological sophistication so that there is no control when someone is free to express opinions in social media. Ironically this freedom is exploited to explore personal and group interests, without seeing the consequences of this dishonourable behaviour. By looking at these various facts, this study presents an effort to provide understanding and education to the public to participate in combating hoax on social media. The purpose of this study is to invite all Christians to contribute and care for the social problems that are troubling society today. Therefore it is time for the role of Christian Religion education to be applied through lifestyles by communicating honestly and get used to using ethics when surfing on social media. Tulisan ini merupakan kajian terhadap peran pendidikan agama kristen dalam memerangi berita hoaks di media sosial. Kajian ini berangkat dari pengamatan penulis secara empiris dimana hari-hari ini berita hoaks di media sosial menjadi berita utama yang tidak habisnya dibicarakan di publik. Akibat dari mewabahnya berita hoaks di media sosial maka tidak sedikit terjadinya perpecahan diantara masyarakat sebagaimana yang diungkapkan dalam tulisan ini seacara empiris. Jika diperhatikan dengan teliti bahwa unsur persolan sebenarnya bukan terletak pada perkembangan ilmu dan teknologi secara global, tetapi persoalannya adalah ada pada setiap oknum yang memanfaatkan teknologi tersebut karena manusia terlalu dimanjakan dengan berbagai fasilitas dari kecanggihan teknologi tersebut sehingga tidak ada kontrol ketika seseorang bebas mengeluarkan berpendapat di media sosial. Dengan melihat berbagai fonomena ini maka tulisan ini hadir sebagai upaya memberi pemahaman dan edukasi kepada masyarakatuntuk ikut berpatisipasi dalam memerangi berita hoaks di media sosial. Tujuan kajian ini mengajak seluruh umat Tuhan untuk berkontribusi dan peduli terhadap persolan-persoalan sosial yang sedang meresahkan masyarakat saat ini.